Simulating Consumers Energy Profiles through Multiagent Systems - Mota, Fernanda P.; Rosa, Vagner S. da; Dimuro, Graçaliz P.; Botelho, Silvia S. da C. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Simulation of home use of electric energy is a very powerful tool for the purpose of studying, planning and managing at electric energy distribution companies. This paper presents a NetLogo-based multi-agent system for energy consumption simulation in residential areas. Several possible consumers profiles and household appliances with different powers are modeled and simulated using computational agents. Simulation results are presented and discussed.